PEMBELAJARAN MENULIS PUISI KELAS VIII SMP NEGERI 6 LABAKKANG - Yuliana Yuliana; Salam Salamn; Mayong Mayong (Universitas Negeri Makassar, 2022)
Learning to Write Poetry for Class VIII Students of SMP Negeri 6 Labakkang. This study aims to obtain a complete and accurate picture of the implementation of learning to write poetry for class VIII students of SMP Negeri 6 Labakkang. The type of research used in this study is a qualitative research using a qualitative descriptive design. Data collection techniques used are observation, interviews, and documentation. The results showed that the material and media components used by the teacher had made the implementation of learning to write poetry well. However, there are still some obstacles that affect learning, one of the different levels of student understanding makes students slow in understanding the material and the lack of variety of media used by teachers.